Competition and privatization : ownership should not matter - but it does - Nellis, John (Revista do IBRAC, 2025)
The benefits of competition, in terms of promoting both efficiency and consumer welfare, are clear and unassailable. In neo-classical economic theory, competition is king; it is the concept that explains how the pursuit of individual self-interest yields outcomes of benefit to society as a whole. All those who have spent time working in private firms and particularly in state enterprises, can cite numerous positive examples of competition's effects, and even more numerous cases where the suppression or absence of competition has led to inefficient and welfare-reducing results. The power and desirability of competition is now solidly established “common ground” for the vast majority of observers of economic life, regardless of their ideological point of departure.